Analyzing the impact of glycemic metabolic status on cardiovascular mortality and all-cause mortality related to the estimated glucose disposal rate: a nationwide cohort study - He, Shiming; Wang, Chao; Huang, Xin; Jian, Guoan; Lu, Zihao; Jiang, Kun; Xie, Guobo; Sheng, Guotai; Zou, Yang (Frontiers in Endocrinology, 2025)
ObjectiveThe Estimated Glucose Disposal Rate (eGDR) serves as a surrogate marker for insulin resistance, with numerous studies highlighting its significant prognostic value. This paper aims to analyze the impact of eGDR on cardiovascular and all-cause mortality across different glycemic metabolic statuses, including normal fasting glucose (NFG), prediabetes, and diabetes.MethodsThis study included 46,016 American adults who underwent health examinations as part of the National Health and Nutrition Examination Survey from 1999 to 2018. Multivariable Cox regression was employed to explore the relationships between eGDR and mortality rates under varying glycemic states. Additionally, Kaplan-Meier curves were used to compare the cumulative incidence of cardiovascular and all-cause mortality across different metabolic statuses. Finally, the predictive value of eGDR for mortality was assessed using receiver operating characteristic curves.ResultsDuring an average follow-up of 115 months, a total of 6,906 (15.01%) participants experienced all-cause mortality, with 1,798 (3.91%) deaths attributed to cardiovascular causes. Kaplan-Meier analysis revealed that higher eGDR levels were associated with gradually reduced mortality rates. After adjusting for confounders, elevated eGDR levels were protective against both cardiovascular and all-cause mortality; the protective effect was notably stronger for cardiovascular mortality [Cardiovascular mortality hazard ratio: 0.92; All-cause mortality hazard ratio: 0.94]. Further interaction tests indicated that glycemic status significantly modified the protective effect of eGDR (P-interaction<0.0001); specifically, high eGDR conferred stronger protection against cardiovascular and all-cause mortality in individuals with NFG and prediabetes compared to those with diabetes. Receiver operating characteristic analysis suggested that eGDR had superior predictive value for mortality in the NFG and prediabetic populations compared to the diabetic group.ConclusioneGDR is a straightforward surrogate for insulin resistance, acting as a protective factor against cardiovascular and all-cause mortality in American adults, with glycemic status modifying this protective effect. Specifically, high eGDR levels offer stronger protection in individuals with NFG and prediabetes compared to those with diabetes; moreover, eGDR appears to be more suitable for predicting mortality events in the NFG and prediabetic populations.